Emission characteristics of polybrominated diphenyl ethers from the thermal disassembly of waste printed circuit boards. (1st April 2020) - Tan, Shufei; Chen, Zhenyu; Wang, Rui; Guo, Jie; Xu, Zhenming
Abstract: Thermal disassembly is prevalently applied for the removal of electronic components on waste printed circuit boards (WPCBs), and temperature is an important factor influencing the pollutant emission process. The emission characteristics of polybrominated diphenyl ethers (PBDEs) to the environment under thermal stress were investigated by conducting both bench-scale experiments and pilot-scale experiments over a temperature range from 100 to 260 °C. Bench-scale experiments showed that the emission factors (EFs) for ∑39 PBDEs from WPCB powder were obviously higher than those from WPCB fragments. Mono-to tri-BDEs predominated the PBDEs emission at each temperature, and the EFs for the mono-to tri-BDEs from WPCB powder ranged from 232 to 3280 ng/g, respectively. Pilot-scale experiments were done to study the particulate matter (PM) and PBDEs emitted from WPCBs mounted with electronic components using a thermal disassembly machine. The mass of the PM and PBDEs released from WPCBs during heating increased with increasing temperature. A bimodal distribution pattern for the PM with peaks at diameters of 0.4–0.7 and 5.8–9.0 μm was observed. The values of the EFs for ∑39 PBDEs varied from 6.41 to 674 ng/g, which were comparable with those calculated from WPCB fragments in the bench-scale experiments. The mass distribution of the ∑39 PBDEs in the PM predominated in the size fraction of >9.0 μm and 0.7–1.1 μm at 100 and 260 °C, respectively. The highly brominated PBDEs (hexa- and hepta-BDEs) had a mass median aerodynamic diameter (MMAD) greater than 2.5 μm, while the lightly brominated PBDEs (mono-to penta-BDEs) were mainly distributed in finer particles, with a MMAD of less than 2.5 μm. The particle size distribution of PBDEs was significantly correlated with the distribution of organic carbon (OC) in PM. All these results can provide basic data for gas pollution related to PBDEs and its control for electronic waste recycling. Graphical abstract: Image 1 Highlights: Emission factors of PBDEs were studied at both bench-scale and pilot-scale tests. The particle size of WPCBs affected the EFs for PBDEs in bench-scale experiments. Higher temperature increased the emission amount of particulate matter and PBDEs. The EFs for particulate PBDEs were greater than those for gaseous-phase PBDEs. Mass median aerodynamic diameter of hexa- and hepta-BDEs were greater than 2.5 μm.